MATH SOLVE

3 months ago

Q:
# If a(x) = 2x - 4 and b(x) = x + 2, which of the following expressions produces a quadratic function? (ab)(x) (StartFraction a Over b EndFraction) (x) (a β b)(x) (a + b)(x)

Accepted Solution

A:

The expressions which produce a quadratic function is the product of the provided binary functions (ab)(x).

What is a quadratic function?A quadratic function is the function in which the unknown variable is one and the highest power of the unknown variable is two. The standard form of the quadratic function is,[tex]f(x)=ax^2+bx+c[/tex]Here,(a,b, c) is the real numbers and (x) is the variable.The two function for the variable x is given as,[tex]a(x) = 2x - 4[/tex][tex]b(x) = x +2[/tex]These are the binary function, and the product of two binary function provide a quadratic function. The product or the multiplication of these two function will provide a quadratic function. Thus,[tex]a(x) b(x)= (2x - 4)(x+2)\\(ab)(x)=2x^2+4x-4x-8\\(ab)(x)=2x^2-8[/tex]Thus, the expressions which produce a quadratic function is the product of the provided binary functions (ab)(x).Learn more about the quadratic function here;

What is a quadratic function?A quadratic function is the function in which the unknown variable is one and the highest power of the unknown variable is two. The standard form of the quadratic function is,[tex]f(x)=ax^2+bx+c[/tex]Here,(a,b, c) is the real numbers and (x) is the variable.The two function for the variable x is given as,[tex]a(x) = 2x - 4[/tex][tex]b(x) = x +2[/tex]These are the binary function, and the product of two binary function provide a quadratic function. The product or the multiplication of these two function will provide a quadratic function. Thus,[tex]a(x) b(x)= (2x - 4)(x+2)\\(ab)(x)=2x^2+4x-4x-8\\(ab)(x)=2x^2-8[/tex]Thus, the expressions which produce a quadratic function is the product of the provided binary functions (ab)(x).Learn more about the quadratic function here;